Granulocyte-Colony Stimulating Factor-Overexpressing Mesenchymal Stem Cells Exhibit Enhanced Immunomodulatory Actions Through the Recruitment of Suppressor Cells in Experimental Chagas Disease Cardiomyopathy - Silva, Daniela N.; Souza, Bruno S. F.; Vasconcelos, Juliana F.; Azevedo, Carine M.; Valim, Clarissa X. R.; Paredes, Bruno D.; Rocha, Vinicius P. C.; Carvalho, Gisele B.; Daltro, Pamela S.; Macambira, Simone G.; Nonaka, Carolina K. V.; Ribeiro-dos-Santos, Ricardo; et al. (Frontiers in Immunology, 2018)
Genetic modification of mesenchymal stem cells (MSCs) is a promising strategy to improve their therapeutic effects. G-CSF is a growth factor widely used in the clinical practice with known regenerative and immunomodulatory actions, including the mobilization of regulatory T cells (Tregs) and myeloid-derived suppressor cells (MDSCs). Here we evaluated the therapeutic potential of MSCs overexpressing G-CSF (MSC_G-CSF) in a model of inflammatory cardiomyopathy due to chronic Chagas disease. C57BL/6 mice were treated with wild-type MSCs, MSC_G-CSF or vehicle (saline) six months after infection with Trypanosoma cruzi. Transplantation of MSC_G-CSF caused an increase in the number of circulating leukocytes compared to wild-type MSCs. Moreover, G-CSF overexpression caused an increase in migration capacity of MSCs to the hearts of infected mice. Transplantation of either MSCs or MSC_G-CSF improved exercise capacity, when compared to saline treated chagasic mice. MSC_G-CSF mice, however, were more potent than MSCs in reducing the number of infiltrating leukocytes and fibrosis in the heart. Similarly, MSC_G-CSF-treated mice presented significantly lower levels of inflammatory mediators, such as IFNγ, TNFα and Tbet, with increased IL-10 production. A marked increase in the percentage of Tregs and MDSCs in the hearts of infected mice was seen after administration of MSC_G-CSF, but not MSCs. Moreover, Tregs were positive for IL-10 in the hearts of T. cruzi-infected mice. In vitro analysis showed that recombinant hG-CSF and conditioned medium of MSC_G-CSF, but not wild-type MSCs, induce chemoattraction of MDSCs in a transwell assay. Finally, MDSCs purified from hearts of MSC_G-CSF transplanted mice inhibited the proliferation of activated splenocytes in a co-culture assay. Our results demonstrate that G-CSF overexpression by MSCs potentiates their immunomodulatory effects in our model of Chagas disease and suggest that mobilization of suppressor cell populations such as Tregs and MDSCs as a promising strategy for the treatment of chronic Chagas disease. Finally, our results reinforce the therapeutic potential of genetic modification of MSCs, aiming at increasing their paracrine actions.